Little environmental dimension, gives reason to an urgent need and sustainable proposal of curricular inclusion - Solano, Dr. Ramón Bedolla; LogamurthieAthiemoolam, Dr.; Rosas, Dra. María Laura Sampedro (IJRDO- Journal of Educational Research, 2017)
The environmental crisis in the world, has promoted the integration of the environmental dimension in education, in this area, are located universities. Resolutions of international summits such as the one organized by the United Nations in Johannesburg in 2002 led to the introduction of the Environmental Dimension in the educational field. Many educational institutions do not. The results of a research conducted in November 2015 at the Nelson Mandela Metropolitan University, School of Education in Port Elizabeth, South Africa, according to the objective "to identify the environmental in the curriculum and the need for its integration", showed that "environmental" does not included, and added to it, a proposal based on the curricular design that includes steps for its inclusion arises. The identification of the environmental, was determined through the results of a survey that was previously reviewed and piloted and that covered the variables (environmental problems, curriculum and environmental competencies), this instrument was applied to the actors of the educational process, study sample. The sample was given through a non-probabilistic approach. It is determined, according to the problem identified, the need to implement the environment as a dimension in the curriculum.